2021
DOI: 10.3390/pr9060962
|View full text |Cite
|
Sign up to set email alerts
|

The Tolerance of Anoxic-Oxic (A/O) Process for the Changing of Refractory Organics in Electroplating Wastewater: Performance, Optimization and Microbial Characteristics

Abstract: In order to investigate the tolerance of an anoxic-oxic (A/O) process for the changing of refractory organics in electroplating wastewater, optimize the technological parameters, and reveal the microbial characteristics, a pilot-scale A/O process was carried out and the microbial community composition was analyzed by high-throughput sequencing. The results indicated that a better tolerance was achieved for sodium dodecyl benzene sulfonate, and the removal efficiencies of organic matter, ammonia nitrogen (NH4+-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…The Intercropping systems showed an increase in beneficial microorganisms ( Pseudomonas, Sphigomonas, Streptomyces, Nocardioides , and SWB02 ) ( Supplementary Table S3 , Figure 4 ), as other authors have observed in different intercropping systems (Yu et al, 2019 ; Zhao et al, 2022 ) Sphingomonas promote nitrogen fixation and dehydrogenation (Leys et al, 2004 ) and has also been found to increase plant growth hormone production (Asaf et al, 2020 ). Some species of Pseudomonas can enhance nutrient uptake and thus plant growth (Franke-Whittle et al, 2015 ; Lami et al, 2020 ) SWB02 , on the other hand, has been linked to the capacity to oxidize nitrite to nitrate (Fumasoli et al, 2015 ; Gao et al, 2021 ), while Niastella ( Supplementary Figure 4B ) can mitigate N 2 0 emissions (Nishizawa et al, 2014 ) Aeromicrobium ( Supplementary Figures 4A , B ) has been linked to plant biomass (Nuzzo et al, 2020 ) and has a greater capability to produce secondary compounds with antimicrobial capacities (Miller et al, 1991 ). These bacteria were highly correlated with TN, TOC, and pH at both sampling times ( Supplementary Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Intercropping systems showed an increase in beneficial microorganisms ( Pseudomonas, Sphigomonas, Streptomyces, Nocardioides , and SWB02 ) ( Supplementary Table S3 , Figure 4 ), as other authors have observed in different intercropping systems (Yu et al, 2019 ; Zhao et al, 2022 ) Sphingomonas promote nitrogen fixation and dehydrogenation (Leys et al, 2004 ) and has also been found to increase plant growth hormone production (Asaf et al, 2020 ). Some species of Pseudomonas can enhance nutrient uptake and thus plant growth (Franke-Whittle et al, 2015 ; Lami et al, 2020 ) SWB02 , on the other hand, has been linked to the capacity to oxidize nitrite to nitrate (Fumasoli et al, 2015 ; Gao et al, 2021 ), while Niastella ( Supplementary Figure 4B ) can mitigate N 2 0 emissions (Nishizawa et al, 2014 ) Aeromicrobium ( Supplementary Figures 4A , B ) has been linked to plant biomass (Nuzzo et al, 2020 ) and has a greater capability to produce secondary compounds with antimicrobial capacities (Miller et al, 1991 ). These bacteria were highly correlated with TN, TOC, and pH at both sampling times ( Supplementary Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%